“Evaluation of Attitude and Practice of the Endodontists and General Practitioners towards Endodontic Instruments Separation” (Journal of Hama University, 2021)
Endodontic instrument separation is an unpleasant mishap, could take place during conservative root canal treatment. This event increases the treatment difficulty significantly. The aim of this research is to evaluate the attitude and practice of general dental practitioners and endodontists towards separated endodontic instruments during treatment procedures. The sample size comprised 232 endodontists and GDPs in Syria, the survey comprised 7 questions about attitude and practice towards endodontic instruments separation, the results showed (87.06%) of respondents had experienced separated instruments with a significantly higher proportion of endodontists (100%) compared with that of GDPs (82.75%), and overall (42.26%) of respondents experienced this problem more than three times. Most of this separations occurred in molars, curved canals and in the apical third of these canals. Only (10.61%) of respondents succeed in retrieval the instrument out of the canal, (38.93%) of them succeed in bypassing it. After collecting the responses data were analyzed using chi-square at the 0.05 level of significance